2006
DOI: 10.1111/j.1463-1326.2006.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation endproducts: what is their relevance to diabetic complications?

Abstract: Glycation is a major cause of spontaneous damage to proteins in physiological systems. This is exacerbated in diabetes as a consequence of the increase in glucose and other saccharides derivatives in plasma and at the sites of vascular complications. Protein damage by the formation of early glycation adducts is limited to lysine side chain and N-terminal amino groups whereas later stage adducts, advanced glycation endproducts (AGEs), modify these and also arginine and cysteine residues. Metabolic dysfunction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
238
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 323 publications
(248 citation statements)
references
References 115 publications
3
238
0
7
Order By: Relevance
“…The chemistry of AGEs is not fully understood; in the meantime increased levels of circulating AGEs have been demonstrated in both animal and human diabetics [9]. AGE structures are associated with many pathophysiological abnormalities [10] as in diabetes and aging [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of AGEs is not fully understood; in the meantime increased levels of circulating AGEs have been demonstrated in both animal and human diabetics [9]. AGE structures are associated with many pathophysiological abnormalities [10] as in diabetes and aging [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicate that AGE products are able at least in vitro to induce activation of various cells including platelets (16,17). In addition to classical glycemic indices, several recent reports indicated that glycated albumin is a relevant and practical biomarker for the progression of diabetic atherosclerosis (18)(19)(20).…”
mentioning
confidence: 99%
“….................................................................................................................................................................................................................................................................................................................................................................................................................................................... In accordance with the results of this study, it would be interesting to investigate whether decline in functional mobility can be attenuated by reducing AGEs levels. Excessive elevation of glucose concentration, such as in DM, most likely accelerates the glycation of proteins (Ahmed and Thornalley, 2007;Rahmadi et al, 2011). Intensive glycaemic control may be a method to decrease AGEs formation.…”
Section: Discussionmentioning
confidence: 99%